Composite solid electrolyte, solid-state battery

By using composite solid electrolytes in lithium-ion batteries and combining MOF materials with lithium salt activation, the problems of safety and energy storage performance of lithium-ion batteries are solved, and higher circulation performance and safety are achieved.

CN119361803BActive Publication Date: 2025-03-18GANZHOU NOVA TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411921534.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The safety of existing lithium-ion batteries is questioned. How to increase battery safety while improving energy storage performance is an urgent problem.

Method used

Using composite solid electrolytes, the MOF material binds closely to the lithium compound by activating specific MOF materials with lithium salts, and increases the lithium ion binding site. The positive electrode side uses heavy metal ion MOF material with a large radius, and the negative electrode side uses light metal MOF material to improve the transmission and interface stability of lithium ions respectively.

Benefits of technology

It improves the cycling performance and ionic conductivity of the battery, enhances the mechanical strength of the solid electrolyte and the stability of the reaction interface, reduces the polarization of the battery, and improves the overall safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361803B_ABST
    Figure CN119361803B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of solid-state batteries, and discloses a composite solid electrolyte and a solid-state battery. The composite solid electrolyte includes a modified solid electrolyte layer on the positive electrode side and a modified solid electrolyte layer on the negative electrode side that are combined together. The modified solid electrolyte layer on the positive electrode side uses a heavy metal ion MOF material with a large radius to provide an additional path for lithium ion transmission, and can also stabilize the interface and reduce the formation of voids during the interface side reaction process. The modified solid electrolyte layer on the negative electrode side uses a light metal MOF material to protect the lithium metal surface, reduce the uncontrollable occurrence of side reactions, and the lower deposition potential of the light metal also reduces the capacity loss caused by excessive deposition of impurity metals. The addition of MOF materials in the solid electrolyte layers on the positive and negative electrode sides increases the mechanical strength of the membrane, reduces the crystallization phenomenon of long-chain polymers, and generally increases the ionic conductivity of the solid electrolyte, while stabilizing the reaction interface and increasing the cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to solid-state electrolytes. Background Art

[0002] High-performance energy storage devices have always been an important research object in the energy field. Lithium-ion batteries, as a representative of chemical energy storage devices, use the migration of lithium ions to store and release charges. They have the advantages of high energy density and long service life and have always been favored in the energy storage field. However, in recent years, with the explosive growth of lithium-ion batteries, the safety of lithium-ion batteries has been questioned by the public due to their flammable electrolytes and uncontrollable thermal runaway. How to increase the safety of lithium-ion batteries while improving their energy storage performance is a problem that is expected to be solved.

[0003] The current main research direction is to use almost non-flammable solid electrolytes to replace liquid electrolytes. Among them, polymer solid electrolytes are currently recognized as the most likely system to achieve large-scale application due to their soft texture and easy processing. However, polymer solid electrolytes have poor ionic conductivity and poor interface stability, and cannot be used on a large scale. Modification of polymer solid electrolytes is the current research focus. Summary of the invention

[0004] In view of the problems existing in the prior art, the main purpose of the present invention is to provide a composite solid electrolyte and its application.

[0005] To achieve the above objectives, the present invention provides the following specific technical solutions.

[0006] First, the present invention provides a composite solid electrolyte, comprising a positive electrode side modified solid electrolyte layer and a negative electrode side modified solid electrolyte layer combined together;

[0007] At least one MOF material selected from ZIF-8, ZIF-67, and UIO-66 is mixed with at least one of lithium carbonate, lithium hydroxide, and lithium fluoride, and then heat-treated in an air atmosphere to obtain a positive electrode side MOF material; the positive electrode side MOF material, polymer, and lithium salt are fully mixed in a solvent to obtain a mixed slurry I; the mixed slurry I is subjected to a film-forming treatment to obtain a positive electrode side modified solid electrolyte layer;

[0008] At least one MOF material among MOF-74 (Mg), Li-BTC-MOF, and UPC-26 is mixed with at least one of lithium carbonate, lithium hydroxide, and lithium fluoride, and then kept warm in air to obtain a negative electrode side MOF material; the negative electrode side MOF material, polymer, and lithium salt are fully mixed in a solvent to obtain a mixed slurry II; the mixed slurry II is subjected to a film-forming treatment to obtain a negative electrode side modified solid electrolyte layer.

[0009] In a further preferred embodiment, when preparing the positive electrode side MOF material, the mass ratio of at least one MOF material among ZIF-8, ZIF-67, and UIO-66 to at least one of lithium carbonate, lithium hydroxide, and lithium fluoride is 1:0.01~0.05.

[0010] In a further preferred embodiment, when preparing the positive electrode side MOF material, the heat treatment temperature is 180-260° C.; the heat treatment time is 3-6 hours.

[0011] In a further preferred embodiment, the concentration of the polymer in the mixed slurry I is 70-130 g / L, the concentration of the MOF material on the positive electrode side is 40-70 g / L, and the concentration of the lithium salt is 60-120 g / L.

[0012] In a further preferred embodiment, the thickness of the modified solid electrolyte layer on the positive electrode side is 100-150 μm.

[0013] In a further preferred embodiment, when preparing the negative electrode side MOF material, the mass ratio of at least one MOF material among MOF-74 (Mg), Li-BTC-MOF, and UPC-26 to at least one of lithium carbonate, lithium hydroxide, and lithium fluoride is 1:0.01~0.05.

[0014] In a further preferred embodiment, when preparing the negative electrode side MOF material, the insulation temperature is 150-220° C.; the insulation time is 1-2 hours.

[0015] In a further preferred embodiment, the concentration of the polymer in the mixed slurry II is 70-130 g / L, the concentration of the MOF material on the negative electrode side is 50-70 g / L, and the concentration of the lithium salt is 60-120 g / L.

[0016] In a further preferred embodiment, the thickness of the modified solid electrolyte layer on the negative electrode side is 75-150 μm.

[0017] In a further preferred embodiment, the polymer is at least one of PVDF, PVDF-HFP, and PVDF-CTFE.

[0018] In a further preferred embodiment, the lithium salt is at least one of LiFSI, LiTFSI, LiFP6, and LiClO4.

[0019] In a further preferred embodiment, the solvent is at least one of N,N-dimethylformamide, N-methylpyrrolidone and tetrahydrofuran.

[0020] In a further preferred embodiment, the film forming process is achieved by blade coating.

[0021] Secondly, based on the same inventive concept, the present invention provides a solid-state battery, comprising the aforementioned composite solid-state electrolyte.

[0022] In a further preferred embodiment, in the solid-state battery, the positive electrode plate, the modified solid electrolyte layer on the positive electrode side, the modified solid electrolyte layer on the negative electrode side, and the negative electrode plate are arranged in sequence.

[0023] The present invention activates a specific MOF material with a lithium salt so that the MOF material is tightly combined with the lithium compound, thereby increasing the lithium ion binding sites in the subsequent solid electrolyte. The modified solid electrolyte layer on the positive electrode side uses a heavy metal ion MOF material with a large radius, and utilizes the large and orderly voids of this type of MOF material to provide an additional path for lithium ion transmission; in addition, this type of MOF material can also be used as a filler to stabilize the interface and reduce the formation of voids during the interface side reaction process. The modified solid electrolyte layer on the negative electrode side uses a light metal MOF material to protect the lithium metal surface and reduce the uncontrollable occurrence of side reactions. The lower deposition potential of the light metal also reduces the capacity loss caused by excessive deposition of impurity metals. The addition of MOF materials in the solid electrolyte layers on the positive and negative electrode sides increases the mechanical strength of the membrane, reduces the crystallization of long-chain polymers, and generally increases the ionic conductivity of the solid electrolyte, while stabilizing the reaction interface and increasing the cycle stability.

[0024] Compared with the prior art, the above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects:

[0025] The present invention designs a modification method which is simple to operate and can realize mass synthesis, and provides a certain reference and basis for future research on the modification of the contact between solid electrolytes and positive and negative electrodes.

[0026] The composite solid electrolyte provided by the present invention can improve the cycle performance and ion conductivity of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The cycle performance diagram of the batteries assembled in Examples 1 to 4 and Comparative Examples 1 to 4.

[0028] Figure 2 These are the EIS curves of the batteries assembled in Test Examples 1 to 4 and Comparative Test Examples 1 to 4. DETAILED DESCRIPTION

[0029] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0030] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0032] Example 1

[0033] (1) Mix the commercial six-series (622) ternary positive electrode material with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, use N-methylpyrrolidone (NMP) as solvent, place the mixture in a small beaker and stir at a speed of 800 r / min for 2 h to obtain a slurry; use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for drying for 4 h, and then obtain a positive electrode sheet after roller pressing.

[0034] (2) Take 10 g of ZIF-8 and 0.25 g of lithium carbonate, mix them thoroughly, and keep them warm at 200 °C in a muffle furnace with air atmosphere for 5 hours to obtain the positive electrode side MOF material.

[0035] (3) Take 10g PVDF-HFP, 5g positive electrode side MOF material, and 9g LiFSI and add them to 100ml N,N-dimethylformamide, stir and mix thoroughly, then apply them on the rolled positive electrode sheet with a 100-micron scraper. After drying, an integrated structure of the positive electrode and the positive electrode side modified solid electrolyte layer is obtained.

[0036] (4) 10 g of MOF-74(Mg) and 0.25 g of lithium carbonate were mixed thoroughly and kept warm at 160° C. for 1.5 hours in a muffle furnace in an air atmosphere to obtain a negative electrode MOF material.

[0037] (5) Take 10g PVDF-HFP, 5g negative electrode MOF material, and 9g LiFSI and add them to 100ml N,N-dimethylformamide, stir and mix thoroughly, and then apply them to the surface of the modified solid electrolyte layer on the positive electrode side of the integrated structure obtained in step (3) with a 75-micron scraper to obtain an integrated structure of the positive electrode and the solid electrolyte layer.

[0038] (6) The integrated structure of the positive electrode and the solid electrolyte layer obtained in step (5) is used as the positive electrode and solid electrolyte of the battery, and the lithium foil is cut into a circular piece with a diameter of 16 mm to serve as the negative electrode. The pieces are placed in a glove box filled with argon atmosphere with a water content and an oxygen content of less than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the electrode during the transfer process, and then assembled into CR2032 button batteries in the glove box.

[0039] Comparative Example 1

[0040] (1) Mix the commercial six-series (622) ternary positive electrode material with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, use N-methylpyrrolidone (NMP) as solvent, place the mixture in a small beaker and stir at a speed of 800 r / min for 2 h to obtain a slurry; use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for drying for 4 h, and then obtain a positive electrode sheet after roller pressing.

[0041] (2) Take 20 g of ZIF-8 and 0.5 g of lithium carbonate, mix them thoroughly, and keep them warm at 200 °C in a muffle furnace with air atmosphere for 5 hours to obtain a MOF material.

[0042] (3) Take 20g PVDF-HFP, 10g MOF material, and 18g LiFSI and add them to 200ml N,N-dimethylformamide, stir and mix thoroughly, then apply them on the rolled positive electrode sheet with a 175-micron scraper. After drying, an integrated structure of the positive electrode and the modified solid electrolyte layer is obtained.

[0043] (4) The integrated structure of the positive electrode and the solid electrolyte layer obtained in step (3) is used as the positive electrode and solid electrolyte of the battery, and the lithium foil is cut into a circular piece with a diameter of 16 mm to serve as the negative electrode. The pieces are placed in a glove box filled with argon atmosphere with a water content and an oxygen content of less than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the electrode during the transfer process, and then assembled into CR2032 button batteries in the glove box.

[0044] Comparative Example 2

[0045] (1) Mix the commercial six-series (622) ternary positive electrode material with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, use N-methylpyrrolidone (NMP) as solvent, place the mixture in a small beaker and stir at a speed of 800 r / min for 2 h to obtain a slurry; use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for drying for 4 h, and then obtain a positive electrode sheet after roller pressing.

[0046] (2) Take 20 g of MOF-74(Mg) and 0.5 g of lithium carbonate, mix them thoroughly, and keep them warm at 160° C. in a muffle furnace with air atmosphere for 1.5 hours to obtain a MOF material.

[0047] (3) Take 20g PVDF-HFP, 10g MOF material, and 18g LiFSI and add them to 200ml N,N-dimethylformamide, stir and mix thoroughly, then apply them on the rolled positive electrode sheet with a 175-micron scraper. After drying, an integrated structure of the positive electrode and the modified solid electrolyte layer is obtained.

[0048] (4) The integrated structure of the positive electrode and the solid electrolyte layer obtained in step (3) is used as the positive electrode and solid electrolyte of the battery, and the lithium foil is cut into a circular piece with a diameter of 16 mm to serve as the negative electrode. The pieces are placed in a glove box filled with argon atmosphere with a water content and an oxygen content of less than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the electrode during the transfer process, and then assembled into CR2032 button batteries in the glove box.

[0049] Comparative Example 3

[0050] (1) Mix the commercial six-series (622) ternary positive electrode material with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, use N-methylpyrrolidone (NMP) as solvent, place the mixture in a small beaker and stir at a speed of 800 r / min for 2 h to obtain a slurry; use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for drying for 4 h, and then obtain a positive electrode sheet after roller pressing.

[0051] (2) Take 10 g of MOF-74(Mg) and 0.25 g of lithium carbonate, mix them thoroughly, and keep them in a muffle furnace with air atmosphere at 160°C for 1.5 hours to obtain the positive electrode side MOF material.

[0052] (3) Take 10g PVDF-HFP, 5g positive electrode side MOF material, and 9g LiFSI and add them to 100ml N,N-dimethylformamide, stir and mix thoroughly, then apply it on the rolled positive electrode sheet with a 100-micron scraper. After drying, an integrated structure of the positive electrode and the positive electrode side modified solid electrolyte layer is obtained.

[0053] (4) Take 10 g ZIF-8 and 0.25 g lithium carbonate, mix them thoroughly, and keep them in a muffle furnace with air atmosphere at 200 °C for 5 hours to obtain the negative electrode side MOF material.

[0054] (5) Take 10g PVDF-HFP, 5g negative electrode MOF material, and 9g LiFSI and add them to 100ml N,N-dimethylformamide, stir and mix thoroughly, and then apply them to the surface of the modified solid electrolyte layer on the positive electrode side of the integrated structure obtained in step (3) with a 75-micron scraper to obtain an integrated structure of the positive electrode and the solid electrolyte layer.

[0055] (6) The integrated structure of the positive electrode and the solid electrolyte layer obtained in step (5) is used as the positive electrode and solid electrolyte of the battery, and the lithium foil is cut into a circular piece with a diameter of 16 mm to serve as the negative electrode. The pieces are placed in a glove box filled with argon atmosphere with a water content and an oxygen content of less than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the electrode during the transfer process, and then assembled into CR2032 button batteries in the glove box.

[0056] Comparative Example 4

[0057] (1) Mix the commercial six-series (622) ternary positive electrode material with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, use N-methylpyrrolidone (NMP) as solvent, place the mixture in a small beaker and stir at a speed of 800 r / min for 2 h to obtain a slurry; use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for drying for 4 h, and then obtain a positive electrode sheet after roller pressing.

[0058] (2) Take 10g PVDF-HFP, 5g ZIF-8 material, and 9g LiFSI and add them to 100ml N,N-dimethylformamide, stir and mix thoroughly, then apply them on the rolled positive electrode sheet with a 100-micron scraper. After drying, an integrated structure of the positive electrode and the modified solid electrolyte layer on the positive electrode side is obtained.

[0059] (3) Take 10g PVDF-HFP, 5g MOF-74 (Mg) material, and 9g LiFSI and add them to 100ml N,N-dimethylformamide, stir and mix thoroughly, and then apply them to the surface of the modified solid electrolyte layer on the positive electrode side of the integrated structure obtained in step (2) with a 75-micron scraper to obtain an integrated structure of the positive electrode and the solid electrolyte layer.

[0060] (4) The integrated structure of the positive electrode and the solid electrolyte layer obtained in step (3) is used as the positive electrode and solid electrolyte of the battery, and the lithium foil is cut into a circular piece with a diameter of 16 mm to serve as the negative electrode. The pieces are placed in a glove box filled with argon atmosphere with a water content and an oxygen content of less than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the electrode during the transfer process, and then assembled into CR2032 button batteries in the glove box.

[0061] Example 2

[0062] (1) Mix the commercial six-series (622) ternary positive electrode material with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, use N-methylpyrrolidone (NMP) as solvent, place the mixture in a small beaker and stir at a speed of 800 r / min for 2 h to obtain a slurry; use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for drying for 4 h, and then obtain a positive electrode sheet after roller pressing.

[0063] (2) Take 10 g of ZIF-67 and 0.1 g of lithium hydroxide, mix them thoroughly, and keep them in a muffle furnace with air atmosphere at 180°C for 6 hours to obtain the positive electrode side MOF material.

[0064] (3) Take 7g PVDF, 4g positive electrode side MOF material, and 10g LiTFSI and add them to 100ml N,N-dimethylpyrrolidone, stir and mix thoroughly, and then apply it on the rolled positive electrode sheet with a 120-micron scraper. After drying, an integrated structure of the positive electrode and the positive electrode side modified solid electrolyte layer is obtained.

[0065] (4) Take 10 g of UPC-26 and 0.3 g of lithium fluoride, mix them thoroughly, and keep them in a muffle furnace in an air atmosphere at 200 °C for 1 hour to obtain a negative electrode side MOF material.

[0066] (5) Take 7g of PVDF, 7g of negative electrode MOF material, and 6g of LiTFSI and add them to 100ml of N,N-dimethylpyrrolidone, stir and mix thoroughly, and then apply them to the surface of the modified solid electrolyte layer on the positive electrode side of the integrated structure obtained in step (3) with a 100-micron scraper to obtain an integrated structure of the positive electrode and the solid electrolyte layer.

[0067] (6) The integrated structure of the positive electrode and the solid electrolyte layer obtained in step (5) is used as the positive electrode and solid electrolyte of the battery, and the lithium foil is cut into a circular piece with a diameter of 16 mm to serve as the negative electrode. The pieces are placed in a glove box filled with argon atmosphere with a water content and an oxygen content of less than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the electrode during the transfer process, and then assembled into CR2032 button batteries in the glove box.

[0068] Example 3

[0069] (1) Mix the commercial six-series (622) ternary positive electrode material with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, use N-methylpyrrolidone (NMP) as solvent, place the mixture in a small beaker and stir at a speed of 800 r / min for 2 h to obtain a slurry; use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for drying for 4 h, and then obtain a positive electrode sheet after roller pressing.

[0070] (2) Take 10 g of UIO-66 and 0.5 g of lithium fluoride, mix them thoroughly, and keep them in a muffle furnace with air atmosphere at 260°C for 3 hours to obtain the positive electrode side MOF material.

[0071] (3) Take 13g PVDF-CTFE, 7g positive electrode side MOF material, and 12g LiFSI and add them to 100ml tetrahydrofuran, stir and mix thoroughly, and then apply them on the rolled positive electrode sheet with a 150-micron scraper. After drying, an integrated structure of the positive electrode and the positive electrode side modified solid electrolyte layer is obtained.

[0072] (4) Take 10 g of Li-BTC-MOF and 0.1 g of lithium carbonate, mix them thoroughly, and keep them in a muffle furnace with air atmosphere at 220 °C for 1 hour to obtain the negative electrode side MOF material.

[0073] (5) Take 13g PVDF-CTFE, 7g negative electrode MOF material, and 12g LiPF6 and add them to 100ml N,N-dimethylformamide, stir and mix thoroughly, and then apply them to the surface of the modified solid electrolyte layer on the positive electrode side of the integrated structure obtained in step (3) with a 150-micron scraper to obtain an integrated structure of the positive electrode and the solid electrolyte layer.

[0074] (6) The integrated structure of the positive electrode and the solid electrolyte layer obtained in step (5) is used as the positive electrode and solid electrolyte of the battery, and the lithium foil is cut into a circular piece with a diameter of 16 mm to serve as the negative electrode. The pieces are placed in a glove box filled with argon atmosphere with a water content and an oxygen content of less than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the electrode during the transfer process, and then assembled into CR2032 button batteries in the glove box.

[0075] Example 4

[0076] (1) Mix the commercial six-series (622) ternary positive electrode material with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, use N-methylpyrrolidone (NMP) as solvent, place the mixture in a small beaker and stir at a speed of 800 r / min for 2 h to obtain a slurry; use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for drying for 4 h, and then obtain a positive electrode sheet after roller pressing.

[0077] (2) Take 10 g ZIF-8 and 0.4 g lithium carbonate, mix them thoroughly, and keep them in a muffle furnace with air atmosphere at 240 °C for 4 hours to obtain the positive electrode side MOF material.

[0078] (3) Take 12g PVDF-HFP, 6g positive electrode side MOF material, and 8g LiFSI and add them to 100ml N,N-dimethylformamide, stir and mix thoroughly, then apply them on the rolled positive electrode sheet with a 120-micron scraper. After drying, an integrated structure of the positive electrode and the positive electrode side modified solid electrolyte layer is obtained.

[0079] (4) 10 g of MOF-74(Mg) and 0.3 g of lithium hydroxide were mixed thoroughly and kept warm at 150° C. for 2 hours in a muffle furnace in an air atmosphere to obtain a negative electrode MOF material.

[0080] (5) Take 12g PVDF, 6g negative electrode MOF material, and 10g LiClO4 and add them to 100ml N,N-dimethylformamide, stir and mix thoroughly, and then apply them to the surface of the modified solid electrolyte layer on the positive electrode side of the integrated structure obtained in step (3) with a 100-micron scraper to obtain an integrated structure of the positive electrode and the solid electrolyte layer.

[0081] (6) The integrated structure of the positive electrode and the solid electrolyte layer obtained in step (5) is used as the positive electrode and solid electrolyte of the battery, and the lithium foil is cut into a circular piece with a diameter of 16 mm to serve as the negative electrode. The pieces are placed in a glove box filled with argon atmosphere with a water content and an oxygen content of less than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the electrode during the transfer process, and then assembled into CR2032 button batteries in the glove box.

[0082] The electrical properties of the button cells obtained in each embodiment and comparative example were tested in the following manner: 100 cycles at a voltage of 2.8-4.3 V and a current density of 0.5 C. The results are shown in FIG. Figure 1As shown. It can be seen that the capacities of the button batteries assembled in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 after 100 cycles are 141.6 mAh / g, 98.1 mAh / g, 105.95 mAh / g, 93.0 mAh / g, and 81.3 mAh / g, respectively; the capacities of the button batteries assembled in Example 2, Example 3, and Example 4 after 100 cycles are 143.5 mAh / g, 148.8 mAh / g, and 145.2 mAh / g, respectively.

[0083] It can be seen from the cycle data of the batteries of Example 1 and Comparative Examples 1-4 that when the solid electrolyte layers on the positive and negative electrode sides are changed, the cycle performance of the battery decreases. The main reason is that heavy metal ions easily undergo replacement reactions with lithium metal on the negative electrode side, and light metals cannot effectively inhibit the dissolution of the positive electrode material. After lithium activation, the MOF material can enhance the surface ion transport performance, increase the ion transport performance of the overall electrolyte, and reduce battery polarization.

[0084] In addition, the positive and negative electrodes in Examples 1 to 4 and Comparative Examples 1 to 4 were replaced with stainless steel sheets with a diameter of 15.6 mm, and assembled into CR2032 batteries in a glove box to obtain Test Examples 1 to 4 and Comparative Examples 1 to 4. The EIS curves of the test batteries at room temperature and a frequency of 100000-1 Hz were as follows: Figure 2 As shown. It can be seen that the Rs of the batteries of Test Example 1, Test Comparative Example 1, Test Comparative Example 2, Test Comparative Example 3, and Test Comparative Example 4 are 14.0Ω, 26.2Ω, 30.6Ω, 28.9Ω, and 33.1Ω, respectively, and the Rs of the batteries of Test Example 2, Test Example 3, and Test Example 4 are 12.6Ω, 16.0Ω, and 14.8Ω, respectively, which also shows that the solid electrolyte layer proposed in the present invention has the function of optimizing the interface and the bulk phase, and can reduce the polarization of the battery.

[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite solid electrolyte, characterized in that: comprising a positive electrode side modified solid electrolyte layer and a negative electrode side modified solid electrolyte layer combined together; At least one MOF material selected from ZIF-8, ZIF-67, and UIO-66 is mixed with at least one of lithium carbonate, lithium hydroxide, and lithium fluoride, and then heat-treated in an air atmosphere to obtain a positive electrode side MOF material; the positive electrode side MOF material, polymer, and lithium salt are fully mixed in a solvent to obtain a mixed slurry I; the mixed slurry I is subjected to a film-forming treatment to obtain a positive electrode side modified solid electrolyte layer; At least one MOF material among MOF-74 (Mg), Li-BTC-MOF, and UPC-26 is mixed with at least one of lithium carbonate, lithium hydroxide, and lithium fluoride, and then kept warm in air to obtain a negative electrode side MOF material; the negative electrode side MOF material, polymer, and lithium salt are fully mixed in a solvent to obtain a mixed slurry II; the mixed slurry II is subjected to a film-forming treatment to obtain a negative electrode side modified solid electrolyte layer.

2. The composite solid electrolyte according to claim 1, characterized in that When preparing the positive electrode side MOF material, the mass ratio of at least one MOF material among ZIF-8, ZIF-67, and UIO-66 to at least one of lithium carbonate, lithium hydroxide, and lithium fluoride is 1:0.01~0.05; when preparing the negative electrode side MOF material, the mass ratio of at least one MOF material among MOF-74(Mg), Li-BTC-MOF, and UPC-26 to at least one of lithium carbonate, lithium hydroxide, and lithium fluoride is 1:0.01~0.

05.

3. The composite solid electrolyte according to claim 1, characterized in that When preparing the positive electrode side MOF material, the heat treatment temperature is 180~260°C, and the heat treatment time is 3~6h; when preparing the negative electrode side MOF material, the insulation temperature is 150~220°C, and the insulation time is 1~2h.

4. The composite solid electrolyte according to claim 1, characterized in that The concentration of the polymer in the mixed slurry I is 70~130g / L, the concentration of the MOF material on the positive electrode side is 40~70g / L, and the concentration of the lithium salt is 60~120g / L; the concentration of the polymer in the mixed slurry II is 70~130g / L, the concentration of the MOF material on the negative electrode side is 50~70g / L, and the concentration of the lithium salt is 60~120g / L.

5. The composite solid electrolyte according to any one of claims 1 to 4, characterized in that The thickness of the modified solid electrolyte layer on the positive electrode side is 100-150 μm; the thickness of the modified solid electrolyte layer on the negative electrode side is 75-150 μm.

6. The composite solid electrolyte according to any one of claims 1 to 4, characterized in that The polymer is at least one of PVDF, PVDF-HFP, and PVDF-CTFE; the lithium salt is at least one of LiFSI, LiTFSI, LiFP6, and LiClO4; and the solvent is at least one of N,N-dimethylformamide, N-methylpyrrolidone, and tetrahydrofuran.

7. A solid-state battery, characterized in that: Comprising the composite solid electrolyte according to any one of claims 1 to 6.

8. The solid-state battery according to claim 7, characterized in that: The positive electrode plate, the positive electrode side modified solid electrolyte layer, the negative electrode side modified solid electrolyte layer, and the negative electrode plate are arranged in sequence.

Citation Information

Patent Citations

  • Solid electrolyte with continuous ion transmission path as well as preparation method and application of solid electrolyte

    CN116315076A

  • Pre-oxidized and vulcanized MOF-based lithium ion battery solid electrolyte and preparation method thereof

    CN118398876A